Environmental treaty secretariats as attention-seeking bureaucracies: The climate and biodiversity secretariats’ role in international public policymaking - Well, M.; Jörgens, H.; Saerbeck, B.; Kolleck, N. (International public administrations in environmental governance: The role of autonomy, agency, and the quest for attention, 2024)
The chapter conceptualizes international public administrations (IPAs) as attention-seeking bureaucracies whose goal is to actively feed their policy-relevant information into the multilateral decision-making process. It suggests two avenues through which international treaty secretariats can attempt to influence international negotiations: (1) Secretariats may attempt to supply policy-relevant information to negotiators from the inside via their close cooperation with the chairs of multilateral negotiations or (2) they may attempt to build support for their preferred policy outputs by engaging with and communicatively connecting actors within the broader transnational policy network in order to exert pressure on negotiators from the outside. Taking the secretariats of the Convention of Biological Diversity and the United Nations Framework Convention on Climate Change as examples, these potential pathways of secretariat influence are illustrated and explored empirically. The findings contribute to a growing body of literature that studies the role of national and international public administrations as agenda-setters, policy entrepreneurs, or policy brokers at the interface of public policy analysis and public administration.